Analysis of lethality of azadirachtin, garlic oil and rotenone against Chrysoperla nipponensis (neuroptera: chrysopidae) - Ruslan, Nurfatin (2016)
Botanical insecticides are widely used nowadays to control insect pest population due to their lower toxicity to human and safer to the environment. However, the use of these insecticides in the field can also affect the population of the beneficial insects. Chrysoperla nipponensis is one of the important beneficial insects and its larvae act as predators. The information on the effects of botanical insecticides to the larvae of C. nipponensis is scarce. The efficacy of three botanical insecticides, azadirachtin, garlic oil and rotenone was tested on the 3rd instar larvae of C. nipponensis based on exposure to insecticide residues in laboratory. The larvae were exposed individually to the insecticide residues for 2 hours and then monitored daily for survivorship over a period of 5 days. The percentage of moribund and dead larvae was recorded to determine the efficacy of insecticides. Garlic oil and rotenone showed an increasing efficacy, in which the percentage of dead and moribund larvae increased by > 10% after 5-d, while azadirachtin showed stable efficacy with variability of toxicity of < 10% after similar period. Lethality index for the botanical insecticides was developed based on quantification of immediate and delayed effects of insecticides exposure on the larvae of C. nipponensis. Garlic oil showed the highest lethality index (23.06%) on the larvae of C. nipponensis, followed by rotenone (20.00%) and azadirachtin (15.00%). The lower index values indicate the three botanical insecticides do not give detrimental effect on the 3rd instar larvae of C. nipponensis.